Calavita's Invitation to Law & Society: Introduction to the Symposium. Issue 1 (January 2014) - Lempert, Richard
<x xml:space="preserve">Abstract</x> This essay introduces a Law & Social Inquiry symposium on Kitty Calavita's book Invitation to Law & Society: An Introduction to the Study of Real Law (2010) that features comments on the law and society enterprise by Jeannine Bell, Austin Sarat, and Christopher Tomlins. It briefly discusses the commentators' views of this enterprise as revealed in their essays and challenges points made by each of them. It goes on to discuss the book's suitability as a student‐oriented introduction to the field of law and society, filling a gap the commentators left open.